Designers' handbook to Eurocode 1 part 1 basics of design - Gulvanessian, H.; Holicky, M. (Eurocode design handbooks., 1996)
This handbook has been compiled to describe the principles and requirements for safety, serviceability and durability of structures explain the basis of design and verification and provide guidelines for related aspects of structural reliability outline the basis and general principles for the structural design of buildings and civil engineering works, including geotechnical aspects.